PENGGUNAAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS X IPS PADA MATA PELAJARAN PENDIDIKAN AGAMA KATOLIK DI SMA ST. ANTONIUS BANGUN MULIA MEDAN - Maria Togatorop, Brenda; Sinulingga, Aldi Alfrianza (Jurnal Bahasa Indonesia Prima (BIP), 2023)
This research aims determine how the use of audiovisual media can enhance the student’s interest in learning in Grade 10 Social Sciences in Catholic Religious Education at St. Antonius Bangun Mulia High School, Medan. This research adopts a qualitative method. The qualitative method is chosen because it allows for an in-depth exploration of a problem and provides detailed explanations regarding the identified problem and its solutions. The data collection techniques employed in this research include interviews, observations, and documentation. The research subjects include one mentor teacher, one peer teacher, and ten students from Grade 10 Social Sciences. The research findings indicate that: 1) The steps of utilizing audiovisual media employed by the Catholic Religious Education teacher are practical. This can be observed from the teacher's competence in carrying out the three pre-learning stages:preparation,planning, and follow-up. 2) using audiovisual media in the classroom has  increased students' interest in learning. This is evidenced by the positive response from the students during teaching sessions and the positive interaction between the teacher and students.